(untitled) (Società e diritti, 2023)
The "Third Sector" has assumed a central role in the most important economies of democratic states. From a comparative perspective, the paper analyzes the principles and regulation on the third sector in France and it traces the phases of the evolutionary process. This research illustrates the transition from the third sector to the social and solidarity economy in France through also the study of the principles of the "loi ESS" of 2014. In particular, it focuses on the relationship between the third sector and "Social and solidarity tourism" in the French system where social and solidarity tourism is increasingly considered a model of integral protection of the person and of equitable and sustainable development.